Troista mediacja przemocy w traumoskryptach na przykładzie tłumaczenia „Kosmosu” Witolda Gombrowicza oraz „Jądra ciemności” Josepha Conrada - Barciński, Łukasz (Przestrzenie Teorii, 2023)
The study deals with the subject of a specific type of crisis i.e. trauma in translation of literary texts. The field of Trauma Studies seems to have a huge research potential if juxtaposed with the discipline of Translation Studies. Many contemporary novels can be analysed from the perspective of traumatic experiences and their representation in works of fiction with special focus on the psychological aspect. Translation process has to make allowances for the hybridity of trauma fiction to recreate it in the target text. The analysis of the rendition of Kosmos by Witold Gombrowicz and Heart of Darkness by Joseph Conrad (works being apt illustrations of the inescapable interfaces of trauma) illustrate the triplicity of mediation of trauma which has to be considered during the translation process: 1. the performative recreation of the original traumatic event, 2. literary texts as inherently traumatic due to the inescapable entry into the symbolic order of linguistic codes, 3. the double bind of the translation process i.e. the trauma of the impossibility of translation.